Decolonising the psychology curriculum: a perspective - Phiri, Peter; Sajid, Sana; Delanerolle, Gayathri (Frontiers in Psychology, 2023)
Decolonisation seeks to reverse the impact of colonisation on minoritised groups. Governments, healthcare institutions, criminal justice and education systems have procedures and protocols deep-rooted in colonisation and operate through a western lens. Decolonisation reaches beyond increasing inclusivity and aims to re-establish history through the experiences and perspective of those most affected. As with many disciplines, core theories, practices and interventions within Psychology, an ethnocentric viewpoint has been used, continuously reinstated through its curriculum. With awareness around diversification and increase in varying demands, it is important that the Psychology curriculum evolves to suit the needs of its’ users. Many recommendations for decolonising the curriculum are trivial surface changes. These involve including required bibliography from diverse minority authors within the modules syllabuses or organising a one-off lecture or workshop from a minority ethnic speaker [2,3]. Some universities have also suggested that lecturers participate in self-awareness practices to ensure they understand decolonisation to appropriately address it through their teaching, whilst others have provided checklists against which they can check the inclusivity of their modules. All these alterations fail to target the root of the problem. To properly reverse the effects of colonisation within the curriculum it would be necessary to re-evaluate the Westernised history that has been retold for years and teach past events through the experiences of those who suffered. Research into how decolonisation can occur in a structured and comprehensive way is necessary to enable the redress for abolition of colonial practices on a global scale.